(untitled) - Nguyen, Thu Phuong (Netherlands, 2014)
Seed dormancy and seed longevity are the most important survival traits in the soil seed bank. Both traits are induced during seed maturation and evolved to assure seed survival during environmental conditions that cannot support the regular course of life. Seed dormancy is related to the timing of germination while seed longevity is involved in retaining germination ability that is gradually lost as a result of aging. The work presented in this thesis aims to identify genetic factors that regulate seed dormancy and seed longevity by generating and exploiting genetic variation.
Keywords: Hạt giống,Seed crops